DEFORMATION MEASUREMENT IN A STEEL BRIDGE SYSTEM BY USING IMAGE PROCESSING METHOD - Firat Alemdar, Zeynep; Bilici, Senem; Alemdar, Fatih (YILDIZ TECHNICAL UNIV, 2018)
In this study, the digital photogrammetry method is described to measure displacements in the experimental mechanics without applying digital sensors to the specimens is described. This optical method uses a camera, a computer with frame grabber board and image analysis methods within the MATLAB Image Processing Toolbox. The displacements at the surface of the test specimens are obtained by the analysis of the movements of special dots painted on the specimen before testing. The image analysis algorithm makes it possible to automatically track the motions of the dots and compute their centroid coordinates in a sequence of images. The aim of the study is to determine the vertical deformation of the steel bridge during testing and to compare with the results obtained from both a traditional instrument and a finite element analysis. Keywords: Steel bridge, deflection measurement, digital image processing.
Keywords: Steel bridge; deflection measurement; digital image processing; Engineering